Agricultural Extension Training and Women's Participation in Ethiopia: Insights from District Level Services - Tarekegne, Chalachew; Dessie, Mulunesh (Ethiopian Journal of Social Sciences, 2020)
Development agents (DAs) are assigned in the local administrations called Kebeles to provide training/advising services to smallholder farmers. In this contribution, the participation of women farmers is compared with that of male farmers in the context of Ankasha district, Awi Zone, Ethiopia. Annual reports on number of trainees were accessed from the district department of Agriculture (2011-2014). Basically, reviewing district reports was done followed by interviewing experts (N=9), DAs (N=6), and organizing 3 Focus Group Discussions with farmers (N=31) each composed of 10-11 individuals. All experts, DAs, and farmers were selected purposively. The Focus Group Discussions were organized in three Kebeles which were selected using lottery method of simple random sampling from 33 Kebeles in the district. To prioritize factors that contributed to low participation of women farmers and to get participant farmers' perceptions, the study used Likert scale type of questionnaire. The results revealed that illiteracy, poor mainstreaming of gender in the agricultural sector and priority to widowed or divorced women farmers as the first, second, and third (respectively) important factors to contribute to low participation of women farmers in the training services provided by the district. Thus, largely, women farmers' participation was found nominal. The extension training and advising services provided by DAs have to consider all women farmers (widowed, divorced, married, and bachelorettes). In the study context, women of all social status are participating in the farming activities of pre-planting, during-planting, and after-planting. And, there is a need to design a training programme in line with these activities for women farmers of all social status. The study will have theoretical contribution to adult learning theory and gender development or mainstreaming. This is the first study to evaluate district level training services as related to the number of women farmer participants in the public agriculture-related education programmes.